(untitled) (Faridpur Medical College Journal, 2016)
The study was undertaken to determine the efficacy and safety profile of Delorme’s procedure as the treatment for full-thickness rectal prolapse. In this study, outcome of Delorme’s procedure for full-thickness rectal prolapse were assessed retrospectively. All the patients who underwent this surgery (22 patients) from July, 2013 to June, 2015 were included in the study. There were 18 males and 4 females with mean age of 37.4 years (range 12-70). The mean operative time was 92.6 minutes (Range 60-180 minutes). There was no mortality and blood loss was minimal. Mean hospital stay was 3.5 days (2-6 days). Outcomes of the procedure were satisfactory and no patient reported recurrence of the disease within the follow up period. Delorme’s operation is safe and effective treatment for complete rectal prolapse in patients of all age and sex. Faridpur Med. Coll. J. Jul 2015;10(2): 55-58